Granulomatous mycosis fungoides with large cell transformation misdiagnosed as leprosy - Sujittra Siriphukpong (2018)
Background: Granulomatous mycosis fungoides is an unusual histopathological variant of cutaneous T-cell lymphoma without clinical distinction from classic mycosis fungoides. Symptoms associated with peripheral nerve involvement have rarely been reported in the literature. Case Report: The authors described a case of granulomatous MF stage IIB with large cell transformation who initially presented with leprosy-like condition and chronic left peroneal neuropathy. The patient received six courses of gemcitabine with greater than 90% improvement of skin lesions. The rest of the lesions were successfully treated with local electron beam radiation. Conclusion: Granulomatous MF with neuropathy can be clinically misdiagnosed if there is no histopathological and immunohistochemical finding to support the diagnosis of lymphoma.